2011
DOI: 10.5194/acp-11-6971-2011
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of isoprene and monoterpenes within a south-east Asian tropical rainforest

Abstract: Abstract. Biogenic volatile organic compounds (BVOCs) emitted from tropical rainforests comprise a substantial fraction of global atmospheric VOC emissions, however there are only relatively limited measurements of these species in tropical rainforest regions. We present observations of isoprene, α-pinene, camphene, -3-carene, γ -terpinene and limonene, as well as oxygenated VOCs (OVOCs) of biogenic origin such as methacrolein, in ambient air above a tropical rainforest in Malaysian Borneo during the Oxidant a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 34 publications
4
35
1
Order By: Relevance
“…Due to observed inter-conversion between MT isomers inside the instrument presumably during 15 the pre-concentration step in the thermal desorption unit, only MT sum is reported. Similar behavior has been observed by Jones et al (2011). However, contrary to their observations we did not find isomerization to be repeatable.…”
Section: Voc Measurementscontrasting
confidence: 56%
See 1 more Smart Citation
“…Due to observed inter-conversion between MT isomers inside the instrument presumably during 15 the pre-concentration step in the thermal desorption unit, only MT sum is reported. Similar behavior has been observed by Jones et al (2011). However, contrary to their observations we did not find isomerization to be repeatable.…”
Section: Voc Measurementscontrasting
confidence: 56%
“…However, PTR-MS is not able to separate different MTs or SQTs. Data on concentrations of individual MTs measured by gas chromatographmass spectrometers (GC-MSs) are scarce and often only from short measurement campaigns (Yanez-Serrano et al 2017, Jardine et al 2015, Jones et al 2011, Hakola et al 2009and 2003, Kesselmeier et al 2002. Emissions of both MTs and SQTs have been studied at various vegetation zones (Guenther et al 2012), but to our knowledge there are only three studies 30 published on atmospheric concentrations of individual SQTs (Bouvier-Brown et al 2009and Yee et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…This is situated within a region that was selectively timber harvested in 1988 (Tangki and Chappell, 2008) and is around 5 km from the protected forest area known as the Danum Valley Conservation Area (DVCA). Measurements of BVOCs taken as part of the OP3 project indicated that the dominant BVOC species observed was isoprene, with an average ground level mixing ratio of around 1 ppb and a maximum value of 2.5 ppb (Jones et al, 2011). Speciated monoterpene mixing ratios were also measured at this location for the first time and indicated a monoterpene to isoprene ratio of around 0.3 (ppb ppb −1 ) during the day and 2.0 at night.…”
Section: Introductionmentioning
confidence: 83%
“…Established measurement techniques for in situ BVOC monitoring typically offer a trade-off between sample frequency and speciation. Detailed information regarding chemical composition may be obtained via conventional gas chromatography methods (GC-FID and GC-MS) which can quantify individual terpene isomers, but with a limited sample frequency (typically one 10-30 min averaged sample, every ∼ 50-60 min -e.g Bouvier-Brown et al, 2009;Jones et al, 2011;Hopkins et al, 2011). In contrast, near real-time terpene observations may be obtained by proton transfer reaction (PTR) mass spectrometry techniques (e.g.…”
Section: E Jones Et Al: a Novel Fast Gas Chromatography Methods Fmentioning
confidence: 99%